Down to the sea : an epic story of naval disaster and heroism in World War II - Henderson, Bruce B., 1946- (Collins, 2008)
Presents the true story of one of the worst Naval combat disasters of World War II when Admiral William Halsey's Third Fleet sailed into a deadly typhoon in the Pacific in December 1944, resulting in the sinking of three ships and damage to twenty-eight other ships, over 140 aircraft, and over 750 men lost at sea.